The Preparedness of English Teachers to Implement Deep Learning in Middle School - Riani, Asma; Sujarwati, Iis (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2025)
The intention of this study is to evaluate the preparedness of junior high school English teachers in Bengkulu Utara to implement deep learning strategies in their classrooms. The application of deep learning methodologies, which emphasize active engagement, critical thinking, and real-world application, purpose to target improvement, communication, and student outcomes. The study applied a structured questionnaire to evaluate the knowledge, skills and attitudes of 50 teachers towards deep learning. The findings indicated that while teachers displayed considerable knowledge (mean = 3.9) and favourable attitudes (mean = 4.1), their competencies in implementing these strategies were less advanced (mean = 3.7). The study's findings underscore the necessity for ongoing professional development to refine teachers' practical skills, especially in the fields of lesson design and technological integration, therefore ensuring the optimal utilization of deep learning in English language pedagogy.